On-surface transmetalation of metalloporphyrins. Issue 45 (8th November 2018) - Hötger, Diana; Abufager, Paula; Morchutt, Claudius; Alexa, Patrick; Grumelli, Doris; Dreiser, Jan; Stepanow, Sebastian; Gambardella, Pietro; Busnengo, H. Fabio; Etzkorn, Markus; Gutzler, Rico; Kern, Klaus
Abstract : Experimental and computational data sheds light onto the metal exchange in porphyrin monolayers. Abstract : Increasing the complexity of 2D metal–organic networks has led to the fabrication of structures with interesting magnetic and catalytic properties. However, increasing complexity by providing different coordination environments for different metal types imposes limitations on their synthesis if the controlled placement of one metal type into one coordination environment is desired. Whereas metal insertion into free-base porphyrins at the vacuum/solid interface has been thoroughly studied, providing detailed insight into the mechanisms at play, the chemical interaction of a metal atom with a metallated porphyrin is rarely investigated. Herein, the breadth of metalation reactions is augmented towards the metal exchange of a metalloporphyrin through the deliberate addition of atomic metal centers. The cation of Fe(ii )-tetraphenylporphyrins can be replaced by Co in a redox transmetalation-like reaction on a Au(111) surface. Likewise, Cu can be replaced by Co. The reverse reaction does not occur, i.e. Fe does not replace Co in the porphyrin. This non-reversible exchange is investigated in detail by X-ray absorption spectroscopy complemented by scanning tunneling microscopy. Density functional theory illuminates possible reaction pathways and leads to the conclusion that the transmetalation proceeds through the adsorption of initially metallic (neutral) Co onto the porphyrin and the expulsion of Fe towards the surface accompanied by Co insertion. Our findings have important implications for the fabrication of porphyrin layers on surfaces when subject to the additional deposition of metals. Mixed-metal porphyrin layers can be fabricated by design in a solvent-free process, but conversely care must be taken that the transmetalation does not proceed as an undesired side reaction.